Los Sistemas Distribuidos Para Optimizar los procesos transaccionales de Registros Académicos en las plataformas de gestión del Aprendizaje de la UTB, durante el 2023. - Sánchez Estrada, Adrián Alexis (2023)
The Technical University of Babahoyo (UTB) faces significant challenges in managing its Academic Records systems due to an increase in student enrollment and academic offerings. These challenges affect the response times and efficiency of the current technological platforms, potentially leading to registration errors and thereby negatively impacting the academic experience. This research project aims to analyze and justify the application of distributed infrastructure systems as a viable and cost-efficient solution to the problems of scalability and robustness. Through detailed analysis, this study proposes that adopting a distributed architecture can improve the efficiency, speed, and resilience of UTB's systems, particularly during high-demand periods like enrollment processes. The research has the potential to position UTB as a leader in technological innovation in the administration of academic systems.